The Implementation of Project Method: Educating Golden Generation or Conservation Nation On Exhibition Subject ECE Department - Diana, Diana; Eka, R Agustinus Arum (Universitas Negeri Semarang, 2015)
The efforts to improve and enhance the quality of education by making curriculum changes, both structural and its formulation procedures would be more meaningful if accompanied by changes in teaching practices that support the successful implementation of the curriculum. One method that can be used is Project Method, whereby it is expected that the quality of student learning experiences in the classroom is more effective and instill the character associated with the environmental, cultural, and natural resources conservation. The purpose and benefits of this research are to provide an overview of procedures or mechanisms of implementation and find out how much the success rate of the method used in learning, especially in exhibition subjects withÃ‚Â project method. This research is a classroom action research with the approach used in this study is a descriptive qualitative approach. The population in this study was all 90 studentsofEarly Childhood Education Department at Semarang State University who are on 6th semester who are taking exhibition subject. The result shows that the procedure of project method activities have to go through stages of actions and observations, which showed at the beginning of the first cycle obtained an average of student ability in this activity amounted to 59.25% and increased in the second cycle achieving 93.08%. It shows that by using the project method, it is very effective to improve the quality of learning for students.How to citeDiana & Eka, R. A. A. (2015). The Implementation of Project Method: Educating Golden Generation or Conservation Nation On Exhibition Subject ECE Department. Indonesian Journal of Early Childhood Education Studies, 4(2), 96-100. doi:10.15294/ijeces.v4i2.9463DOI 10.15294/ijeces.v4i2.9463